Introduction to Special Edition Honoring Gerry Schamess. Issue 2 (2nd July 2020) - Rasmussen, Brian; Mishna, Faye
Abstract: Gerry Schamess was an outstanding figure in the field of clinical social work over the past 50 years. His contribution to the field is recognized in this introduction and in the articles that follow.